Development of Shooting and Dribbling Skill Test Instruments for U-23 Futsal Players in Central Java Province - Kustiawan, Andri Arif; Hidayatullah, M. Furqon; Purnama, Sapta Kunta; Umar, Fadilah (Migration Letters, 2023)
A futsal basic skills measurement tool with excellent validity and reliability in test shooting and test dribbling was created as a result of this research to be used in the teaching and training of U-23 futsal sports. The research design employed was development research, with procedures for formulating initial product types/models for PORPROV Surakarta futsal players aged 18 to 23 years, with as many as 15 players for small groups and 90 PORPROV players for group trials. This is made up of the six districts of Banyumas Regency, Klaten Regency, Kebumen Regency, and Kendal Regency. The validity, reliability, and norms of the product skills test were then evaluated. Validity and dependability tests for small-scale instruments consisting of the basic skills of the shooting test obtained a value of 0.959 and the shooting retest obtained a value of 0.971 while the reliability test was 0.979. The dribbling validity test for the test was obtained at 0.968 and for the retest was 0.964 with a reliability of 0.893. The results of the large-scale validity of the basic skills of test shooting obtained a value of 0.948 and a retest obtained a value of 0.988 while the reliability test was 0.971. The results of the large-scale validity on the basic skills of the dribbling validity test for the test were obtained at 0.995 and for the retest at 0.995 with a reliability of 0.990, so it can be said that a reliable measuring instrument will still produce the same relative value even though it is carried out at different times. There is no difference between the small group and the large group in the U-23 futsal test shooting and test dribbling basic skill norms so the measuring instrument can be said to be objective.